2022
DOI: 10.1021/acsomega.2c03614
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Pahae Natural Zeolite–Cocoa Shell Activated Charcoal Nanofilter as a Water Adsorber in Bioethanol Purification

Abstract: Pahae natural zeolite potentially can be used as a filtration material because of its high adsorption capacity. However, it is known that other supportive materials such as activated charcoal are needed to optimize the utilization of natural zeolite as an adsorber. This study aims to investigate the potential use of activated charcoal which was synthesized from cocoa shells waste and natural zeolite in nanosize as the adsorber in order to increase the concentration of bioethanol. The mixing process of nanozeol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Many studies have shown that carbon-based materials like activated carbon can be used as an effective absorbent for the removal of organic materials such as methylene blue in a high capacity 31 , 32 . The large surface area of carbon-based materials also support their ability in capturing heavy metals 33 , 34 . Recently, several studies have indicated that zeolite and activated carbon made from mechano-synthesis can be used in environmental applications 35 37 .…”
Section: Introductionmentioning
confidence: 93%
“…Many studies have shown that carbon-based materials like activated carbon can be used as an effective absorbent for the removal of organic materials such as methylene blue in a high capacity 31 , 32 . The large surface area of carbon-based materials also support their ability in capturing heavy metals 33 , 34 . Recently, several studies have indicated that zeolite and activated carbon made from mechano-synthesis can be used in environmental applications 35 37 .…”
Section: Introductionmentioning
confidence: 93%
“…As per the analysis findings, using hydrothermal zeolited activated employed as a filling material within the filter is acknowledged to enhance the water absorption capacity. The water absorption value is positively correlated with the porosity level, suggesting that greater pores or cavities in the zeolite lead to higher water absorption rates [15][16][17][18].…”
Section: Water Adsorption Testingmentioning
confidence: 99%
“…Outside the zeolite, positively charged ions (cations) like Mg 2+ , Ca 2+ , Na + , K + balance the negative charge within the pores [12]. These cations are weakly bonded to the aluminosilicate structure through electrostatic interactions, allowing them to be exchanged with other cations in solution [13][14][15]. The unique structure of natural zeolites enables them to excel in cation exchange, adsorption, and molecular sieving processes.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite, characterized by an abundance of pores and channels, is another effective adsorbent. The cylindrical shape of zeolite's pores and channels enhances its surface area, and greater pore density corresponds to increased overall surface area [9][10][11][12][13][14]. A prior study demonstrated the efficacy of cocoa husk adsorbent in reducing iron (Fe) and manganese (Mn) content by 97.59% and 90.95%, respectively [15].…”
Section: Introductionmentioning
confidence: 99%